Keratinocytes express functional CARD18, a negative regulator of inflammasome activation, and its altered expression in psoriasis may contribute to disease pathogenesis. (May 2016) - Göblös, Anikó; Danis, Judit; Vas, Krisztina; Bata-Csörgő, Zsuzsanna; Kemény, Lajos; Széll, Márta
Highlights: The basal CARD18 level is higher in psoriatic non-involved epidermis compared to healthy epidermis. CARD18 induction ability differs in healthy and in psoriatic skin. CARD18 is expressed in keratinocytes: we are first to demonstrate its expression in a non-professional immune cell type. CARD18 silencing decreases the expression of inflammasome components and increases the IL-1β secretion of keratinocytes under inflammatory conditions. Abstract: Caspase recruitment domain family member 18 (CARD18, Iceberg) is known as a negative regulatory molecule that inhibits inflammatory events by terminating inflammasome activation due to a direct interaction with pro-caspase-1. During the investigation of molecular mechanisms in keratinocytes that contribute to the pathogenesis of psoriasis, we found that CARD18 expression differs in healthy and psoriatic skin; moreover, CARD18 demonstrated altered response under inflammatory conditions in healthy and psoriatic skin. In healthy skin, low basal CARD18 expression was detected, which showed significant elevation in response to inflammatory stimuli (lymphokine treatment or mechanical injury). In contrast, higher basal expression was observed in psoriatic non-involved skin, but no further induction could be detected. We demonstrated that keratinocytes express CARD18 both at mRNA and protein levels and the expression increased in parallel with differentiation. The investigation of cellular inflammatory processes revealed that psoriasis-associated danger signals triggered the expression of inflammasome components (AIM2, Caspase-1) and CARD18 as well as IL-1β production of keratinocytes. Furthermore, gene-specific silencing of CARD18 in cells treated with cytosolic DNA (poly(dA:dT)) resulted in increased IL-1β secretion, suggesting a negative regulatory role for CARD18 in keratinocyte inflammatory signaling. The differential regulation of CARD18 in healthy and psoriatic uninvolved epidermis may contribute to the susceptibility of psoriasis. Furthermore, our in vitro results indicate that CARD18 may contribute to the fine tuning of keratinocyte innate immune processes.